Elaboration and optimization of Iron Oxide thin films deposited via spray pyrolysis. Applications in water treatment - Bekkar, Dhaouia (University of Eloued جامعة الوادي, 2021)
In this work, firstly structural, optical, and morphological properties of Cobalt doped alpha phase iron oxide (hematite: Co-α-Fe2O3) thin films has been carried out. Secondly, Co-α-Fe2O3 and their applications in the area of wastewater treatment and antibacterial were tested. 0.25-1.5 and 2-20wt. % Co-α-Fe2O3 thin films have been deposited on 500°C heated glass via spray pyrolysis with moving nozzle (SPMN). For all 0.25-1.5wt. % Co-α-Fe2O3 thin films XRD analysis exhibit the presence of diffraction peaks corresponding to (012), (104), and (110), planes of αFe2O3 phase. The average grain size changes with doping concentration, it reaches 38.81nm for 1.5 wt. % Co doping. FTIR study confirms the existence of Fe-O bonds of α-Fe2O3, with enhanced hydroxyl radical OH on the surface of Fe2O3. Such hydroxyl radical OH is a good result for Photocatalytic application. Photocatalytic activities of 0.25-1.5wt. % Co-α-Fe2O3 samples were studied based on the degradation of methylene blue (MB). This activity increases with cobalt doping concentration, and it is better under sunlight irradiation. For antibacterial test, the doping concentration was varied from 2 to 20wt. %. Analyzing XRD pattern indicated the presence of diffraction peaks corresponding to plans (012), (104), (110), (113), (024), (116), (214), and (300) which signified the hematite phase formation. As a result of doping, two added peaks were appeared and much well with (200) and (311) planes, of Cobalt oxides CoO and Co3O4, respectively. The peak positions correspond to hematite marked a fixed slight shift to lower 2θ values. Crystalline size increases in the beginning of doping then decreases with doping concentration. SEM images demonstrate that the clusters of grain size are homogeneous with some agglomerating sites. The average grain sizes clusters are: 166, 200, 227, and 225 nm for 2, 5, 10, and 20wt. %, respectively. The synthesized cobalt doped hematite nanoparticles exhibit an antibacterial activity against E. coli, Listeria innocua, Pseudo mona saeruginosa and Salmonella enteric beyond 5wt. % Co/Fe doping. في بداية هذا العمل، تم تحديد الخصائص التركيبية والضوئية والمورفولوجية للشرائح الرقيقة للطور الفا ألكسيد الحديد )الهيماتيت( المطعم بالكوبالت: Fe2O3-α-Co ،ومن ثم اختبار العينات المطعمة في مجال معالجة المياه الملوثة وكمضادات للبكتيريا. تم ترسيب شرائح رقيقة من أكسيد الحديد المطعم بالكوبالت بالنسب الوزنية ) 25.0-5.1 )٪و)2-20 )٪على شرائح زجاجية عبر تقنية الرش باالنحالل الحراري بفوهة متحركة )SPMN )تحت درجة حرارة 500 درجة مئوية. يُظهر تحليل طيف االشعة السينية -بالنسبة لجميع الشرائح المطعمة بالنسب 25.0-5.1-٪وجود قمم حيود موافقة للمستويات البلورية )012( ، )104( ، )110 ، )مما يؤكد تبلور أكسيد الحديد طور ألفا Fe2O3-α .يتغير متوسط الحجم الحبيبي مع تركيز نسب التطعيم، ويقدر بـ: 81.38 نانومتر من أجل الشرائح المطعمة بنسبة 5.1 .٪تؤكد دراسة مطيافية االشعة تحت الحمراء وجود الروابط O-Fe للمركبFe2O3- α ، كما أن التطعيم يعزز وجود مركبات الهيدروكسيل على سطح الشرائح والتي تعد نتيجة جيدة من أجل نشاطية التحفيز الضوئي. تمت دراسة فعالية التحفيز الضوئي للعينات بنا ًء على تحلل أزرق الميثيلين، حيث أظهرت النتائج أن النشاطية تزداد مع تركيز نسبة التطعيم، ويكون أفضل تحت إشعاع أشعة الشمس. بالنسبة الختبار أكسيد الحديد كمضاد للبكتيريا، تم تطعيم العينات بالنسب الوزنية: 2- 20 .٪أشار تحليل طيف االشعة السينية إلى وجود قمم حيود مقابلة للمستويات )012 )و )104 )و )110 )و )113 )و )024 )و )116 )و )214 )و )300 )والتي تشير إلى تكون طور الهيماتيت، كما ظهرت قمتان تابعتان للمستويات )200 )و )311 )نتيجة للتطعيم، والتي تقابل أكاسيد الكوبالت CoO و Co3O4 على التوالي. يزداد الحجم الحبيبي في بداية التطعيم ثم يتناقص تباعا مع زيادة نسبة التطعيم ليصل الى 63.28 نانومتر. توضح صور المسح االلكتروني )SEM )أن حجم الحبيبات متجانسة مع وجود بعض المواقع للتجمعات. متوسط الحجم الحبيبي قدر بـ : 166 ، 200 ، 227 ، 225 نانومتر للنسب الوزنية 2 ، 5 ، 10 ، و 20 ٪ على التوالي. ُ بالكوبالت نشاطً coli. E و Listeria أظهرت جزيئات الهيماتيت النانوية المطعمة ا مضا ًدا للبكتيريا ضد innocua و monasaeruginosa Pseudo و enteric Salmonella وذلك من أجل نسب تطعيم تتجاوز . ٪5
Thesis of Doctorate In Physics Specialty Rayanemment and material
Keywords: α-Fe2O3; thin films; doping; Photocatalytic activity; antibacterial test; Fe2O3-α ، التطعيم، االغشية الرقيقة ، نشاطية التحفيز الضوئي ، اختبار مضادات البكتيريا